Optic neuritis in a teenage girl with granulomatosis with polyangiitis - Bokonjić, Dejan; Avram, Nada; Minić, Predrag; Radosavljević, Aleksandra (Vojnosanitetski pregled, 2021)
Introduction. Granulomatosis with polyangiitis (GPA), formerly known as Wegener’s granulomatosis, is characterized by necrotizing granulomatous inflammation in various tissues, including blood vessels, but primarily in the respiratory tract and kidneys. Clinical manifestations can be diverse, including inflammation of the eye and adnexa. Optic neuritis is a very rare ophthalmological manifestation of GPA, not previously described in a teenager. Case report. We presented a case of a 16-year-old girl with a rare extrapulmonary manifestation of GPA. The girl had a previous history of GPA and complained of a sudden blurred vision in the left eye. She was promptly referred to an ophthalmologist who noted a decreased visual acuity of 20/400 in the left eye. Colour vision was impaired in the spectrum of red colour. Clinical examination revealed normal anterior segment findings. On ophthalmoscopy, the left optic nerve oedema was noted. Urgent computed tomography of the left orbit showed a soft tissue mass around the optic nerve in the apex of the orbit. Magnetic resonance imaging confirmed the diagnosis of optic perineuritis. After pulse doses of methylprednisolone, the girl achieved complete resolution of vision in the left eye. Conclusion. If untreated, inflammation of the optic nerve can lead to a permanent loss of vision. Prompt diagnostic and adequate treatment of patients with GPA is needed in order to prevent vision-threatening complications and control the systemic disease.